New technique for sharpening ultra-thin wires for the drawing process: incremental furnace stretching - Kustra, Piotr; Milenin, Andrij (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
In the wire drawing process, the wire is subjected to sharpening before each drawing. Traditional methods for sharpening wires involve one of the following techniques: crimping, grinding, rolling, chemical etching, or stretching within a furnace. Wire sharpening becomes especially difficult in the manufacture of ultra-thin wire. This study proposes and examines a novel technique for sharpening thin and ultra-thin wires through specialized stretching in a furnace. This study proposes and investigates a new technique for sharpening thin and ultra-thin wires based on stretching them in the furnace. Using a rheology-based concept of wire deformation during stretching, this study offers a substantial enhancement in the maximum attainable thinning of the wire during sharpening. Technically, this advancement is achieved by transitioning from a single-stage stretching process to an incremental one, characterized by small increments of deformation at each stage. In addition to incremental stretching, the proposed method includes simultaneous movement of the wire through a continuous micro furnace, repeated at each stage of elongation, which achieves thinning of the wire end of a given length. This study theoretically and experimentally explores further potentialities of this approach concerning the fabrication of ultra-thin wire. The findings show that the effectiveness of the proposed method strongly depends on the shape of the stress-strain curve of the wire material. For example, the conducted research demonstrated that this method is more effective for brass than for copper wire.